2017
DOI: 10.1371/journal.pone.0174398
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit enhances the transmission of plant viruses by insect vectors

Abstract: Drought is a major threat to crop production worldwide and is accentuated by global warming. Plant responses to this abiotic stress involve physiological changes overlapping, at least partially, the defense pathways elicited both by viruses and their herbivore vectors. Recently, a number of theoretical and empirical studies anticipated the influence of climate changes on vector-borne viruses of plants and animals, mainly addressing the effects on the virus itself or on the vector population dynamics, and infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
1
37
0
1
Order By: Relevance
“…This prediction holds only if the bacterial transmission rate is similar between drought‐stressed and well‐watered plants. A recent study demonstrated that transmission of Cauliflower mosaic virus and Turnip mosaic virus to turnip Brassica rapa by the aphid M. persicae increased with drought stress (van Munster et al ., ). Similar research should be conducted on citrus and C Las to have a better understanding of how drought stress affects spread of this pathogen.…”
Section: Discussionmentioning
confidence: 97%
“…This prediction holds only if the bacterial transmission rate is similar between drought‐stressed and well‐watered plants. A recent study demonstrated that transmission of Cauliflower mosaic virus and Turnip mosaic virus to turnip Brassica rapa by the aphid M. persicae increased with drought stress (van Munster et al ., ). Similar research should be conducted on citrus and C Las to have a better understanding of how drought stress affects spread of this pathogen.…”
Section: Discussionmentioning
confidence: 97%
“…Impacts of temperature, water deficit and variable light also influence responses to viruses in A. thaliana (Xu et al ., ; Hily et al ., ). In turnip, drought was shown to enhance the rate of transmission for Cauliflower mosaic virus (CaMV) and TuMV (van Munster et al ., ), whereas the opposite was found in transmission of Turnip yellows virus (TuYV) in A. thaliana (Yvon et al ., ). Together, these results highlight the need to capture the variable stresses within and between days that typify natural environments.…”
Section: Introductionmentioning
confidence: 99%
“…Plant viruses, the major pathogens causing emerging infectious disease (Anderson et al, 2004), exhibit environmental sensitivity of diverse components of their epidemics and thus represent a relatively large threat in the context of global change. For example, recent studies have reported the impacts of high temperatures, water deficit, variable light and CO 2 concentration changes on both rates of infection and transmission efficiencies of viruses (Xu et al, 2008;Nancarrow et al, 2014;Chung et al, 2015;Hily et al, 2016;van Munster et al, 2017;Trebicki et al, 2017;Yvon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation water does not affect the several viral pre-infection stages that are found within the fungi and bacteria life cycles. When lacking or in excess, water and irrigation may cause physiological host changes, which may accentuate or attenuate symptoms or alter the relationship of the vector with the virus and the host plant [43]. In some cases, the virus may protect its host from severe drought by avoiding irreversible wilt, as reported by Xu et al [44].…”
Section: Vectors Of Plant Viruses Have a Major Role On The Epidemics mentioning
confidence: 96%